Precariously housed: Daily life struggles under provisional housing in Landskrona, Sweden - Adner Gustafsson,Amanda (2025)
This thesis draws on experiences of seven informants living in Landskrona, Sweden, whom I interviewed in 2017. The informants had an on-going or recent experience of being precariously housed, under the following arrangements: a shelter, informal housing (rented without any contract), sublease, a hostel, and housing under a so-called special contract. Besides being precarious, these arrangements also serve as provisional solutions for housing; the informants express that they would like to move to another housing, but find themselves with few options to do so. In this thesis, I draw on Dorothy E. Smith’s generous conception of work, informed by feminist practice and thinking, to construct an extended definition of housing consumption. Housing consumption, as I define it here, refers to the ways that the informants navigate the interactions, laws and policies of the housing market. The analysis focuses on relations which have shaped the informants’ recent experiences of housing consumption. First, it explores how the informants’ struggles with housing relate to other struggles in their lives: struggles related to domestic violence, struggles related to migration and so-called bordering, and struggles within the realm of health and health care. Second, it looks into how the informants navigate relations to intermediaries and gatekeepers in the context of their provisional housing, and how their daily lives are impacted by the terms of such housing. Third, the analysis ends with a section on how the informants view the possibility of accessing other housing options while living under provisional housing, how they imagine their future, and how their housing situation shape their view of themselves and of life as a whole.
Keywords: housing precariousness; neoliberalism; institutional ethnography; domestic violence; migration; health; eviction